Distribution-led growth through methodological lenses - Michaelis Nikiforos (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
This paper presents a methodological discussion of two recent "endogeneity" critiques of the Kaleckian model and the concept of distribution-led growth. From a neo-Keynesian perspective, it is criticized because it treats distribution as quasi-exogenous, while in Skott (2017), distribution is viewed as endogenously determined by a series of (exogenous) institutional factors and social norms, and therefore one should focus on these instead of the functional distribution of income per se. The paper discusses how abstraction is used in science and economics, and uses the criteria proposed by Lawson (1989) for what constitutes an appropriate abstraction. Based on this discussion, it concludes that the criticisms are weak, although the issues raised by Skott provide some interesting directions for future work within the Kaleckian framework.
Keywords: B22; B41; B50; E11; E12; 330; Kaleckian model; distribution-led; abstraction; closure